Use of 3D Non-Contact Profilometry to Quantify Indent Characteristics of Prestressing Wires Used in Pretensioned Concrete Railroad Ties - Haynes, Mark; Wu, Chih-Hang; Beck, B. Terry; Peterman, Robert J. (Rural Railroad Safety Center, Kansas State University., 2021)
The objective of this research was to investigate possible correlation between prestressing wire indent geometry and the performance of pretensioned concrete members fabricated with these same reinforcements. Thirteen (13) commercially available and twelve (12) custom-made reinforcement wires were evaluated. A new non-contact indent profiling system was developed to collect detailed surface profiles of the prestressing steel. New geometrical feature measurements and processing algorithms were developed to provide detailed measurement of prestressing steel according to the dimensioning and tolerancing guidelines of ASME Y14.5-2009. These geometrical features were found to have significant correlation with the transfer length and fracture propensity of concrete crossties. Models were created to predict the transfer length of concrete crossties based on the extracted indent characteristics.
Keywords: Indented Prestressing Wire; ASTM A881; 3D Non-Contact Profilometry; Concrete Railroad Ties; Profilometer